Bioinformatic analysis of biological pathways in coronary heart disease and Alzheimer’s disease - N. Y. Chasovskikh; E. E. Chizhik (Бюллетень сибирской медицины)
Aim. Using bioinformatic tools, to perform a pathway enrichment analysis in Alzheimer’s disease and coronary heart disease (CHD).Materials and methods. Genes contributing to susceptibility to CHD and Alzheimer’s disease were obtained from the public database DisGeNET (Database of Gene – Disease Associations). A pathway enrichment analysis was performed in the ClueGO Cytoscape plug-in (version 3.6.0) using hypergeometric distribution and the KEGG and Reactome databases.Results. The identified genes contributing to susceptibility to Alzheimer’s disease and CHD are included in 69 common signaling pathways, grouped into the following subgroups: cell death signaling pathways (1); signaling pathways regulating immune responses (2); signaling pathways responsible for fatty acid metabolism (3); signaling pathways involved in the functioning of the nervous system (4), cardiovascular system (5), and endocrine system (6).Conclusion. Following the performed analysis, we identified possible associations between processes involving genetic factors and their products in CHD and Alzheimer’s disease. In particular, we assumed that susceptibility genes involved in the implementation of these pathways regulate apoptosis, production of inflammatory cytokines and chemokines, lipid metabolism, β-amyloid formation, and angiogenesis.